Evaluation of a Witch Hazel Extract for the Potential Prebiotic and Protective Effect on Select Lactiplantibacillus plantarum (Prev. Lactobacillus plantarum) Strains - Failla, Morgan; Lee, Jungyun; Rasooly, Reuven; Apostolidis, Emmanouil (Frontiers in Nutrition, 2022)
Witch hazel extract has been evaluated in prior studies demonstrating the phenolic-mediated biofilm inhibition, toxin production inhibition and growth inhibition in Staphylococcus aureus. In this study we are evaluating the possible prebiotic and protective effect of witch hazel extract on select probiotic Lactiplantibacillus plantarum strains, namely L. plantarum LP 10241 and L. plantarum LPBAA-793. When the prebiotic effect was evaluated, we observed that the tested extract had prebiotic effect at the higher tested dose (0.5%) on LPBAA-793 strain (8.7 log CFU/mL after 18 hrs compared to 5.1 log CFU/mL with the control) and on LP 10241 strain (7.7 log CFU/mL after 18 hrs compared to 4.4 log CFU/mL with the control). For the evaluation of the protective effect of witch hazel extract on the select strains, we subjected nutrient depletion stress under aerobic conditions and monitored the cell death with and without addition of witch hazel extract. We observed that the tested extract had a significant protective effect on LPBAA-793 strain (4 log CFU/mL after 12 days, compared to no growth with control) and a slighter protective effect against LP 10241 strains (6.3 log CFU/mL in day 2 compared to 4.3 log CFU/mL with control). The results from this research provide for the first time the rationale that while witch hazel extract has significant antimicrobial, anti-toxin production and anti-biofilm activities on pathogenic microorganisms, it might play an important and positive role on health-beneficial probiotic bacteria.